2010
DOI: 10.2478/s11536-009-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

Platelet indices in patients with colorectal cancer

Abstract: AbstractThe interaction between cancer cells and platelets has been known for a long time. Although platelet indices have been also investigated in several clinical settings, it has not been exactly demonstrated in cancer patients. We investigated platelet indices in colorectal cancer patients and compared with healthy subjects. Two hundred and twenty-one colorectal cancer patients and 110 healthy subjects were enrolled into the retrospective study. Data were obtained from comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…According to literature data, studies concerning colorectal cancer and MPV yield divergent results. A study conducted by Karagöz et al [82] showed a higher platelet count in colorectal cancer patients as compared to healthy subjects and lack of differences in MPV between the study group and control. Moreover, no changes were noted in MPV between patients with and without colorectal cancer metastases.…”
Section: Mpv In Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…According to literature data, studies concerning colorectal cancer and MPV yield divergent results. A study conducted by Karagöz et al [82] showed a higher platelet count in colorectal cancer patients as compared to healthy subjects and lack of differences in MPV between the study group and control. Moreover, no changes were noted in MPV between patients with and without colorectal cancer metastases.…”
Section: Mpv In Carcinomamentioning
confidence: 99%
“…Moreover, no changes were noted in MPV between patients with and without colorectal cancer metastases. MPV was not found to correlate with cancer location and advancement [82]. On the other hand, research performed by Li et al [20] demonstrated a significantly higher MPV level in colorectal cancer patients than in healthy subjects.…”
Section: Mpv In Carcinomamentioning
confidence: 99%
“…Hasil penelitian berbeda dengan penelitian Toka B dkk dan Karagoz dkk di Turki bahwa tidak terdapat perbedaan jumlah trombosit pada pasien kanker kolorektal nonmetastasis dan metastasis. 17,18 Penelitian Josa di Eropa didapatkan peningkatan jumlah trombosit preoperatif merupakan marker yang signifikan untuk OS yang buruk. 9 Penelitian Zu di China tahun 2018 memperlihatkan jumlah trombosit meningkat pada kanker kolorektal dibanding adenoma/pasien sehat.…”
Section: Hasilunclassified
“…19 Namun, hasil penelitian ini berbeda dengan penelitian Karagoz dkk bahwa kadar PDW tidak berbeda pada kanker kolorektal nonmetastasis dan metastasis. 18 Begitu juga dengan penelitian Toka B, dkk di Turki yang melakukan penelitian tentang perubahan kadar PDW pada pasien kanker kolon yang mendapat kemoterapi, hasilnya yaitu tidak terdapat perbedaan kadar PDW pada pasien kanker kolorektal metastasis dan pasien kanker kolorektal nonmetastasis. 17 Pada penelitian Zhu di China didapatkan kadar PDW meningkat pada kanker kolorektal dibanding orang sehat, namun kadar PDW lebih rendah pada kanker kolorektal dibanding adenoma kolorektal.…”
Section: Hasilunclassified
“…Higher values of PDW indicate labile volumetric difference when compared with normal individuals. PDW has been associated with poor prognosis in many cancers including hepatocellular,[ 5 ] pancreatic,[ 6 7 ] malignant melanoma,[ 8 ] thyroid,[ 9 10 ] laryngeal[ 11 ] colorectal,[ 12 13 14 ] gastric,[ 15 ] non-small cell lung carcinoma[ 16 ] and endometrial carcinoma. [ 17 ] Studies of PDW association with GBC are scarce.…”
Section: Introductionmentioning
confidence: 99%